Hybrid power production for a grid with limited capacity - Wahlström,Oscar; Andersson,Filip (2025)
There is an urgent need to reduce CO2 emissions in Sweden, primarily caused by industry and the transport sector, which together accounted for nearly 65% of the country's total CO2 emissions in 2023. A key solution to this challenge is the rapid and effective implementation of green electrification, which involves transitioning industry and transportation to electricity and electricity-based fuels. As a result, Sweden is projected to experience a dramatic increase in electricity demand by 2030. This raises crucial questions, including how the grid will handle this surge and which electricity sources are best suited to meet the demand. The thesis explores how hybrid parks, a relatively new power source combining photovoltaic (PV) panels, wind turbines, and battery energy storage systems (BESS), can be an important part of this transition. This study investigates the advantages and disadvantages of hybrid parks by designing a hypothetical case study. It guides the reader through the challenges and solutions a hybrid park can offer through four steps in park development: screening, technology selection and park design, energy production analysis, profitability analysis, and the Swedish electricity market analysis. The methodology involves literature studies, interviews, production simulations, and economic analysis. Given the rapid changes in the Swedish electricity market and technology, particularly in recent years, it is important to note that literature older than five years may already be outdated. With this in mind, the results presented in this report should be viewed as a snapshot of the current electricity system. The study highlights several critical measures and challenges that are important to consider when designing future hybrid and energy parks. The results also support the future relevance of hybrid parks as a production source in Sweden's energy mix. Some of these key findings are as follows: * Grid capacity, a major obstacle slowing Sweden's electrification, necessitates prioritizing grid availability over land area or geology in the screening process to facilitate production connections. * The significant reduction in the costs of Variable Renewable Energy (VRE) and BESS technologies increases their profitability, positioning them and hybrid parks for important roles in the future electricity mix. * The negative correlation between solar and wind power generation helps stabilize overall power output. * Flexibility in output power and electricity provided by BESS allows for strategies such as curtailment and load shifting, which integrate more production and substantially boost profitability through various revenue streams and cost savings. The findings suggest that hybrid parks represent a promising investment opportunity, enabling the expansion of variable renewable energy sources with minimal compromise to grid stability compared to wind power and solar pV alone. These facilities are expected to become more common, establishing themselves as the new standard for VRE development. VRE installations lacking flexibility will quickly become obsolete.
Keywords: Energy; Batteries; Solar PV; Wind power; Power; Hybrid; Hybrid park; Tariffs; GreenGo Energy; Grid; Flexibility; Electricity; BESS; DSO; TSO; Curtailment; Electricity markets